Exploring the Experiences and Coping Strategies of Divorcees and their Children in Asogli State of the Volta Region - Dogbey Alice Emmanuella; Amos Amuribadek Adangabe; Florence Kazi (Integrated Journal for Research in Arts and Humanities, 2022)
The study was conducted to explore the lived experiences of divorcees, children of divorce, and the coping strategies they employed in dealing with their situations. This is a qualitative study that adopted descriptive phenomenological approach. A total of 20 respondents comprising 14 divorced women and men, 6 children of divorcee were used in the study and sampled through snowball and purposive sampling techniques. Data was gathered using semi-structured interview, and focused group discussion guides. The study revealed that the divorcees experienced physical, mental, social and financial problems. Children of the divorcee significantly experienced stress, emotional pains, sorrow, and worry about their condition. Again, the study revealed that divorcees and children of divorcee faced many consequences, they were not aware of availability of counselling services that could help them. It was recommended, among others, that divorcees who are mostly single parents must be given marital counselling and/or post-traumatic stress management. Again, the establishment of community-based counselling centres in the Asogli state for this purpose would be laudable. Finally, the District Assembly, traditional rulers in the Asogli state, Civil Society Organisations, and government agencies should offer care and support services to divorcees and their children including scholarships to children from divorced homes.